The politics of the pile: Material imagination and improvisation in the 1871 Paris Commune - Douglas, Carl (Interstices: Journal of Architecture and Related Arts, 2022)
In the Paris Commune of 1871, collectives, collective action, and shared spaces were imagined through metaphors of mounding and scattering. This article explores the material imagination that underlies these metaphors and several improvised urban constructions through which they manifested. In particular, it refers to a mound of sticks and manure built to cushion the fall of the monumental Vendôme Column, heaps of meaningless consumer goods, impromptu barricades piled up in the streets, stellar matter imagined by Auguste Blanqui, conjugations of terms in poems by Arthur Rimbaud, and ultimately the piled bodies of the Communards themselves. This shared preoccupation, I suggest, enabled collective improvisation and the “articulation work” of cobbling together a new public world (Star and Strauss, 1999: 10).